O semiotyczno-kulturowych uwarunkowaniach niektórych figur w przemówieniach patriarchy Cyryla - Sadowski, Jakub (Przegląd Rusycystyczny, 2017)
This article is the semotic and cultural analysis of Patriarch Kirill’s speeches at conferences and meetings of the World Russian National Council. Such speeches are not only a part of the policy of the Russian Orthodox Church — which remains in a particular relationship with the official policy of the Russian state, but — making an appeal to the Russian cultural identity — also aspire to be the synthetic approach, to show most important things for the Church. In doing so, they must refer to those parts of the Russian semiotic universe that are most recognizable to users of culture — as a sign of “selfdescription”. The recipient of a message, by “finding himself” in this construct of identity, also can better understand the ideological level of message. Therefore, ideological constructs tend to have unusually abundant cultural background. This article focus on the background of those ideological constructs, which are very current topic in the official discourse of the Russian Orthodox Church in recent years — such as “The Russian Civilization” and “The Russian World”.